Portable Incinerator Capacity of 5000 Grams with Used Fuel Oil - Herraprastanti, Eva Hertnacahyani; Saputra, Yudis Martin Shindu; Suryanto, Hendri; Ashraf, Muhammad Arif (Universitas PGRI Semarang, 2024)
Waste is a significant problem that needs to be urgently addressed. If waste is left untreated and disposed of improperly, it can become contaminated by bacteria, viruses, and other toxins that pose serious risks to humans. In this study, researchers designed and created a portable incinerator that utilizes used oil fuel. The study aimed to determine the highest temperature that can be achieved when incinerating wet and dry waste at weights of 5000 grams, 3000 grams, and 1000 grams. Additionally, performance of portable incinerator was evaluated based on the combustion rate and fuel consumption. The result show that the maximum temperature generated by both dry and wet waste is 450 degrees Celcius. The maximum volume of waste that can be loaded into the combustion chamber is 5000 grams. The results show that the maximum combustion rate of the portable incinerator for dry waste weighing 1000 grams is 196.85 gr/s.The maximum burning rate for wet waste weighing 1000 grams is 165.56 gr/s. The minimum fuel consumption produced from dry waste weighing 1000 grams is 300 ml of used oil. And the maximum fuel consumption is produced from wet waste weighing 5000 grams, namely 1000 ml of used oil.